2011
DOI: 10.1039/c0cs00173b
|View full text |Cite
|
Sign up to set email alerts
|

Non-invasive tools for measuring metabolism and biophysical analyte transport: self-referencing physiological sensing

Abstract: Biophysical phenomena related to cellular biochemistry and transport are spatially and temporally dynamic, and are directly involved in the regulation of physiology at the sub-cellular to tissue spatial scale. Real time monitoring of transmembrane transport provides information about the physiology and viability of cells, tissues, and organisms. Combining information learned from real time transport studies with genomics and proteomics allows us to better understand the functional and mechanistic aspects of ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(25 citation statements)
references
References 71 publications
0
25
0
Order By: Relevance
“…This different behavior was not unexpected, as PIN2 is not expressed in Arabidopsis hypocotyls (Chen et al, 1998). Moreover, in vivo measurements of auxin flow in the root tips showed that the root apex transition zone (0.1 to 0.3 mm from the root tip in Arabidopsis; Verbelen et al, 2006;Baluš ka et al, 2010) is the most active region with respect to polar auxin flow Baluš ka et al, 2010;McLamore et al, 2010;McLamore and Porterfield, 2011) and gravity-stimulated peak cell elongation rates (Chavarria-Krauser et al, 2008). A BL illumination significantly increased the peak value of the auxin flux rate in the root apex transition zone of both dark-grown wildtype and pin2 seedlings, among which the response of the pin2 mutant was less significant than that of the wild type.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This different behavior was not unexpected, as PIN2 is not expressed in Arabidopsis hypocotyls (Chen et al, 1998). Moreover, in vivo measurements of auxin flow in the root tips showed that the root apex transition zone (0.1 to 0.3 mm from the root tip in Arabidopsis; Verbelen et al, 2006;Baluš ka et al, 2010) is the most active region with respect to polar auxin flow Baluš ka et al, 2010;McLamore et al, 2010;McLamore and Porterfield, 2011) and gravity-stimulated peak cell elongation rates (Chavarria-Krauser et al, 2008). A BL illumination significantly increased the peak value of the auxin flux rate in the root apex transition zone of both dark-grown wildtype and pin2 seedlings, among which the response of the pin2 mutant was less significant than that of the wild type.…”
Section: Discussionmentioning
confidence: 99%
“…Measurement of the rhizosphere auxin flux reflex activity of cell-to-cell auxin transport, which occurs in the apoplast, provides a quantitative analysis of polar auxin transport (McLamore et al, 2010;McLamore and Porterfield, 2011). A carbon nanotube auxin-selective microelectrode was used to monitor auxin fluxes in Arabidopsis roots as described previously Santelia et al, 2005;Bouchard et al, 2006;Bailly et al, 2008;Kim et al, 2010).…”
Section: Measurement Of Auxin Flow In the Root Apex Regionmentioning
confidence: 99%
“…Real-time, non-invasive monitoring of cellular processes from cell cultures has received increased interest in the past decades [39,22,40]. Electrochemical sensors can provide a wide range of information on biophysical and biochemical events.…”
Section: In Vitro Electrochemical Detection Of Alp Secreted From Cancmentioning
confidence: 99%
“…Molecules that are directly relevant to metabolism (e.g., oxygen, adenosine triphosphate), homeostasis (e.g., H + , Na + , K + , Ca 2 + ), and cell signaling (e.g., nitric oxide, glutamate, dopamine) can be measured using these techniques. Over the past years there have been intensive efforts to develop non-invasive tools for cellular microphysiology monitoring [22,23]. Due to demonstrated sensitivity and non-invasiveness, electrochemical detection methods have been applied for cell-based investigation [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…Potentiometric electrodes are available for common physiological ions (Na ) and for organic anions such as salicylate and organic cations such as tetraethylammonium. In addition, amperometric electrodes and/or optrodes have been developed for molecules such as oxygen, glucose and nitric oxide (Smith et al, 2007;McLamore and Porterfield, 2011).…”
Section: Introductionmentioning
confidence: 99%